(untitled) (Ustozlar uchun, 2025)
This article provides a comprehensive analysis of the role and significance of the STEAM (Science, Technology, Engineering, Art, Mathematics) approach in the modern education system. Unlike traditional education, it highlights STEAM’s role in ensuring interdisciplinary integration, fostering critical and creative thinking among students, and developing skills to find engineering solutions to complex problems. Additionally, the article examines the methodological foundations for implementing STEAM education into the school curriculum, international experiences, and the prospects for its development within the educational system of Uzbekistan.